Pengaruh Literasi Keuangan dan Pengendalian Diri Terhadap Perilaku Konsumtif Siswa - Ariria, Dhania Ni’ma; Ulfatun, Titik (Jayapangus Press, 2025)
This study aims to analyze the influence of financial literacy and self-control on the consumptive behavior of 10th and 11th grade Accounting and Finance students at SMK Negeri 6 Surakarta. High consumptive behavior among students can affect their personal financial management in the future. This study uses a quantitative method with a survey approach, where data were collected through questionnaires distributed to 141 students selected using the Slovin formula. The variables studied include financial literacy (X1), self-control (X2), and consumptive behavior (Y). The data collected were analyzed using multiple regression with the help of SPSS 22. The results of the study indicate that financial literacy positively influences consumptive behavior, meaning that the higher the students' financial literacy, the more likely they are to spend money consumptively. On the other hand, self-control negatively influences consumptive behavior, showing that students with better self-control tend to be more prudent in managing their expenditures. Regression tests show that both variables significantly affect students' consumptive behavior. This study concludes that good financial literacy can encourage consumptive behavior, but high self-control can reduce this tendency. The limitation of this study lies in its focus on only two variables, so it is recommended that future research include additional relevant variables to gain a more comprehensive understanding.